Fiscal Rules and Government Size in the European Union - Jochen O. Mierau; Eduard Suari Andreu (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies the impact of national fiscal rules on government size as measured by the ratio of government expenditures to gross domestic product. We develop a model of the budgetary process and show that a common pool problem may arise which can be mitigated through fiscal rules. We test the model's predictions using a novel time-series cross-section dataset of 27 European Union members for the period between 1990 and 2011. Corroborating the model, we find that fiscal rules have a negative impact on government size. Contrasting the model, their impact becomes smaller as the number of ministers increases.
Keywords: H11; H61; E61; 330; political fragmentation; fiscal rules; government size